Traçados de vida de jovens privadas de liberdade em Minas Gerais - Tatiana Maria Marques Tironi (2021)
Despite the rapid growth of female incarceration, such agenda is present in an embryonic form in academic discussions though yet absent in the feminist movements. The aim of the study was to figure the ways young women in deprivation of liberty represent and build the female gender in their daily experiences, based on their practices and experiences, including infractions, in a stage prior to their caution. It’s meant to be a qualitative study that uses Oral History as a research method. Twelve young females from Centro Socioeducativo São Jerônimo, whom were deprived of liberty from October to November 2020 took part in the study. Life narratives were analyzed using content analysis technique, from which six themes emerged: i. Family dynamics: single parenthood, poverty and domestic violence; ii. Fragility of the bond with formal education; iii. Experiences of sexual exploitation and child labor; iv. Mental suffering and drug use; v. Scarcity of leisure activities; vi: Male influence and female protagonism in infractions. Experiences of oppression, violence, class and gender inequalities, which highlights the importance of an intersectional understanding of the phenomenon, were observed as result. This relational reading of the daily life and ordinary experiences of those young women theoretically contributes to the field of occupational sciences for the analysis of daily activities and practices embedded in a social texture. Finally, it points out the need for specific public actions and policies for gender-sensitive youth, which contribute to the deconstruction of stereotyped and sexist social constructions.